2003
DOI: 10.1176/appi.ajp.160.9.1606
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cortical Folding in Schizophrenia: An MRI Morphometric Study

Abstract: These results from a larger patient group confirm a previous report of reduced cortical folding in schizophrenia patients. They also suggest a distinct pattern of abnormality between schizophrenia subtypes regarding the process of cerebral lateralization and are in agreement with the neurodevelopmental hypothesis of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
82
0
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 30 publications
8
82
0
13
Order By: Relevance
“…Indeed, studies conducted in non-syndromic schizophrenic patients have shown that alterations in connectivity (Oertel-Knöchel et al, 2014), cortical thickness (Oertel-Knöchel et al, 2013;Padmanabhan et al, 2015), and cortical volume (Padmanabhan et al, 2015) in temporal brain regions are related to high positive symptoms, while alterations in white matter volume (Sanfilipo et al, 2000), surface area (Padmanabhan et al, 2015), and cortical volume (Benoit et al, 2012;Koutsouleris et al, 2008;Sigmundsson et al, 2001) in frontal and temporal brain regions are related to high negative symptoms. A decrease in gyrification throughout the entire brain has also been reported when comparing non-syndromic patients with schizophrenia to healthy participants (Sallet et al, 2003). Moreover, non-syndromic subjects at risk for developing schizophrenia also present morphological alterations, specifically changes in cortical volume in the temporal (Job et al, 2006(Job et al, , 2005 and prefrontal regions (Job et al, 2005(Job et al, , 2002) when compared to healthy controls.…”
Section: Introductionmentioning
confidence: 78%
“…Indeed, studies conducted in non-syndromic schizophrenic patients have shown that alterations in connectivity (Oertel-Knöchel et al, 2014), cortical thickness (Oertel-Knöchel et al, 2013;Padmanabhan et al, 2015), and cortical volume (Padmanabhan et al, 2015) in temporal brain regions are related to high positive symptoms, while alterations in white matter volume (Sanfilipo et al, 2000), surface area (Padmanabhan et al, 2015), and cortical volume (Benoit et al, 2012;Koutsouleris et al, 2008;Sigmundsson et al, 2001) in frontal and temporal brain regions are related to high negative symptoms. A decrease in gyrification throughout the entire brain has also been reported when comparing non-syndromic patients with schizophrenia to healthy participants (Sallet et al, 2003). Moreover, non-syndromic subjects at risk for developing schizophrenia also present morphological alterations, specifically changes in cortical volume in the temporal (Job et al, 2006(Job et al, , 2005 and prefrontal regions (Job et al, 2005(Job et al, , 2002) when compared to healthy controls.…”
Section: Introductionmentioning
confidence: 78%
“…Both reduced (e.g. Sallet et al, 2003) and increased (e.g. Falkai et al, 2007) GI have been found using manual or automated methods on coronal sections of MR images, and one study did not find significant group differences (Highley et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Cortical folding abnormalities in schizophrenia measured using the gyrification index (GI) methodology (Zilles et al, 1988) have been reported in post-mortem (Vogeley et al, 2000) and MRI studies (Harris et al, 2004a;Harris et al, 2004b;Kulynych et al, 1997;Sallet et al, 2003). Since the GI measures the ratio of inner and outer cortical surface contours, these studies were limited to analyses of brain slices in different lobes.…”
Section: Introductionmentioning
confidence: 99%